(untitled) (PANGEEA, 2025)
Amber and amber-like materials are often found nowadays in Romanian gemstone exhibitions. Fake amber is more and more difficult to detect, because modern manufactured products made of natural resins and/or polymers are so perfect that they can produce the same esthetic effects as transparent and colored amber pieces. Macroscopically, they cannot be separated from amber without a good personal experience or only applying gemological classic tests. Therefore, modern physico-chemical methods, such as Fourier Transform infrared spectroscopy (FT-IR) and X-ray diffractometry (XRD) are applied to discriminate amber and forgeries.